Cross-Generational Enculturation of Keroncong in Semarang (Universitas Negeri Semarang, 2022)
Keroncong is a native Indonesian music which has some influences from Portuguese. The development of Keroncong in Indonesia is considered to be in decline. The decline in the development of Keroncong is caused by the lack of media in socializing and the reduced number of Keroncong activists who still exist. One of the efforts to conserve Keroncong is through enculturation. This research discusses the enculturation pattern that is formed by combining several methods of enculturation which are performed and implemented by three elements Keroncong Semarang in order to suppress the decline rate of Keroncong development. This research uses cultural approach to examine the problems. The method used in this research was the analytical qualitative method. Data collection techniques used were observation, interviews, and literacy studies. The interviews were conducted directly with the informants, which are Sri Haryani, Sumarsono, and Nunung Nurjanah as Keroncong activists and practitioners, Marco Marnadi (Head of Congrock 17) and Ibnu Amar Muchsin (Head of Orkes Keroncong Tetap Segar) as Keroncong groups, and Drama, Dance, and Music Education study program at Universitas Negeri Semarang as educational institution in Semarang in the time span of three months. To test the validity of the data, extended observation steps and in-depth interviews were also utilized. The result of this research all three elements of Semarang Keroncong with their own methods of enculturation forms an intersection of which become the pattern of Semarang Keroncong enculturation. Individual element, groups element, and educational institution element utilize direct teaching as one of method used in enculturating value and skill of Keroncong.